2023
DOI: 10.1039/d2sc06315h
|View full text |Cite
|
Sign up to set email alerts
|

Doping of charge-transfer molecules in cocrystals for the design of materials with novel piezo-activated luminescence

Abstract: A novel piezo-activated luminescent material with wide range modulation of the luminescence wavelength and a giant intensity enhancement upon compression was prepared using a strategy of molecular doping. The doping...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The shortened separations hint at improved hydrogen-bond strength when water serves as a hydrogenbond acceptor. These {(CzIp) 3 S3). Each carbazole moiety along the noncovalent ribbon has produced face-to-face π•••π stackings with OFN or TCNQ, and the centroid-to-centroid (Table S4) and interplanar distances are 3.7005(15) and 3.7391(2) Å as well as 3.5270(10) and 3.5270(10) Å.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shortened separations hint at improved hydrogen-bond strength when water serves as a hydrogenbond acceptor. These {(CzIp) 3 S3). Each carbazole moiety along the noncovalent ribbon has produced face-to-face π•••π stackings with OFN or TCNQ, and the centroid-to-centroid (Table S4) and interplanar distances are 3.7005(15) and 3.7391(2) Å as well as 3.5270(10) and 3.5270(10) Å.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Molecular crystals with desirable structures and efficient photoluminescence are highly important for multiscenario field applications in displaying, 1,2 sensing, 3,4 optical waveguide, 5 and optoelectronics devices. 6−10 Lots of organic crystalline materials with tunable emission color, long-lived lifetime, and/or high quantum yield have been designed and manufactured by powerful cocrystal engineering strategy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The authors have further demonstrated that doping small fractions of pyrene into TCNB/naphthalene cocrystals led to a FRET system that yielded white light . These preliminary investigations have been followed by numerous reports of stoichiometric cocrystal development between donors and acceptor molecules to design multicolor emissive solids. Though charge transfer cocrystals based on donar–acceptor conjugated molecules and halogen bonds are well reported, hydrogen bond-driven cocrystals are rarely reported to tune the optoelectronic properties. …”
Section: Introductionmentioning
confidence: 99%
“…High-pressure can be used to precisely tune intermolecular interactions, altering molecular vibration and rotation modes and electronic excited states, and thus manipulating the emission behaviors. [39][40][41][42][43][44] It is also an efficient technique to tune the delocalization of p electrons and amplify the related effects that are weak at ambient pressure. In this study, we discovered that the "transannular effect", [45][46][47] a type of weak p-p interaction, occurs in phenanthrene molecular crystals because of their unique molecular conguration.…”
Section: Introductionmentioning
confidence: 99%